Successful extraction of a large airway foreign body using flexible bronchoscopy and electrocautery snare in a post-COVID-19 patient with difficult airway anatomy: a case report - Lu, Yugang; Dong, Jiawei; Gu, Ye (Frontiers in Medicine, 2025)
A 64-year-old man presented with a 10-cm metal spoon handle retained in his airway for 40 years—a rare case of chronic foreign body aspiration in an adult. The condition was further complicated by post-COVID-19 respiratory symptoms and challenging airway anatomy, including a short thyromental distance and Mallampati Class IV classification. The patient complained of persistent chest tightness, shortness of breath, and recurrent respiratory issues that persisted after recovering from COVID-19. Initial attempts at removal using rigid bronchoscopy (RB) failed due to anatomical limitations. However, the foreign body was successfully extracted via flexible bronchoscopy (FB) using an electrocautery snare, without airway injury or bleeding. The patient's symptoms resolved immediately, and he was discharged within 24 h, showing sustained improvement at a 3-month follow-up. This case underscores the importance of pre-procedural airway assessment to anticipate technical challenges and the need for procedural adaptability. When RB fails, FB with advanced tools such as electrocautery snares can serve as an effective alternative. RB and FB should be seen as complementary techniques, and clinical teams should be prepared to use both, along with appropriate innovations. Moreover, the case highlights FB's expanding role in managing complex, chronic airway foreign bodies and the critical role of flexibility, planning, and specialized tools in achieving optimal outcomes.